First Thought : Conversations with Allen Ginsberg - Ginsberg, Allen, 1926-1997 (Book collections on Project MUSE., 2017)
Here through previously uncollected interviews, we encounter Allen Ginsberg elaborating on how speech, as much as writing and reading, and even poetry, is an act of art. Revealing, enlightening, and often just plain entertaining, Allen Ginsberg in conversation is the quintessential twentieth-century American poet as we have never before encountered him: fully present, in pitch-perfect detail.